Correlação entre diferentes indicadores de adiposidade corporal e atividade física habitual em jovens do sexo masculino - Fernandes, Rômulo Araújo [UNESP]; de Oliveira, Arli Ramos; Freitas Jr., Ismael Forte [UNESP] (My University, 2006)
The purpose of this study was to analyze the relationship between different body fat indicators, habitual physical activity and exposure to sedentary behavior in pre-adolescent males. The sample involved 60 subjects from 10 to 14 years old. The used body fat indicators were: the Body Mass Index, waist circumference, the sum of eight skinfolds, and estimation of percent of body fat using bioelectric impedance. The indicators of physical activity and sedentary behavior were assessed through a questionnaire. Descriptive statistical procedures were: mean, medium, standard deviations, minimum and maximum values, as well as the Spearman correlation. The SPSS software was used and P values lower than 5% were considered statistically significant. None of the body fat indicators presented significant correlation (p> 0.05) with indicators of habitual physical activity, although, all of them were moderately associated with time spent in sedentary activities (Body Mass Index: r= 0.42, waist circumference: r= 0.43, sum of skinfolds: r= 0.43 and percent of body fat: r= 0.43). Therefore, it is concluded that exposure to sedentary behavior correlates with body composition in pre-adolescent males aged 10 to 14 years.
Correlation between different body fat indicators and habitual physical activity in boys
Keywords: Body composition; Obesity; Physical activity